If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -7 + -1(-2x) = 3 + -2x Remove parenthesis around (-2x) 3x + -7 + -1 * -2x = 3 + -2x Multiply -1 * -2 3x + -7 + 2x = 3 + -2x Reorder the terms: -7 + 3x + 2x = 3 + -2x Combine like terms: 3x + 2x = 5x -7 + 5x = 3 + -2x Solving -7 + 5x = 3 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -7 + 5x + 2x = 3 + -2x + 2x Combine like terms: 5x + 2x = 7x -7 + 7x = 3 + -2x + 2x Combine like terms: -2x + 2x = 0 -7 + 7x = 3 + 0 -7 + 7x = 3 Add '7' to each side of the equation. -7 + 7 + 7x = 3 + 7 Combine like terms: -7 + 7 = 0 0 + 7x = 3 + 7 7x = 3 + 7 Combine like terms: 3 + 7 = 10 7x = 10 Divide each side by '7'. x = 1.428571429 Simplifying x = 1.428571429
| -3=-5x-8+5 | | -55=6+7x | | 4a+5x=0 | | 15x-3(2x-1)=3(x-5) | | (6x-8)(x+1)= | | -28=-7 | | -55=3x-4x-6 | | 2z-23=-31 | | 9k+5K=15K-1 | | 4-k+3=12-4k | | 3i+4=5 | | x^2+y^2+8x+16y=41 | | -55=-3x-4x-6 | | -7(4-6n)=140 | | 5-3K=12-4 | | 6n+9=3n-21-6 | | -9-6x+x=31 | | 7x+5+7x=-23 | | 702-498= | | 200=8(1+4b) | | log(2)(5x+5)=3 | | Uax+but=c | | -9-2x+4x=15 | | 9/18-10/18 | | 3x+8+3x=8 | | 4cos(x)=sec(x) | | 4t^2+24t-35=0 | | 9y-5= | | 4t^2+24-35=0 | | 12A/b-5b/3 | | -7=r-11 | | (5a^5/2b^5)^2 |